Learning styles and achievement in first-year university students - González Lomeli, Daniel (2000)
A structural model of students' appraisals about their own learning strategies and the effects of these strategies on their school scores is presented. Self-reports of 229 new first-year-students of a public university were analized using a structural equations method. Participants responded to a learning-style questionnaire, and their final first semester course scores were also recorded. The measurement model confirmed the existence of acquisition, memory resources managing, and information processing strategies, very much alike those proposed by Castañeda (1995). Since the model explained only the 7% of the school achievement, the modeling of the dependent latent variable, conformed by a set of observed variables, is stressed and debated.